2010
DOI: 10.3390/s100706275
|View full text |Cite
|
Sign up to set email alerts
|

Study on Additional Carrier Sensing for IEEE 802.15.4 Wireless Sensor Networks

Abstract: Wireless sensor networks based on the IEEE 802.15.4 standard are able to achieve low-power transmissions in the guise of low-rate and short-distance wireless personal area networks (WPANs). The slotted carrier sense multiple access with collision avoidance (CSMA/CA) is used for contention mechanism. Sensor nodes perform a backoff process as soon as the clear channel assessment (CCA) detects a busy channel. In doing so they may neglect the implicit information of the failed CCA detection and further cause the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
19
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…The discrete time Markov chain (DTMC) models to analyze the IEEE 802.15.4 have been studied in [11][12][13][14][15]. Park et al [11] analyzed the throughput and energy consumption under saturated condition and validated their analysis through comparison with simulations.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…The discrete time Markov chain (DTMC) models to analyze the IEEE 802.15.4 have been studied in [11][12][13][14][15]. Park et al [11] analyzed the throughput and energy consumption under saturated condition and validated their analysis through comparison with simulations.…”
Section: Related Workmentioning
confidence: 99%
“…Pollin et al [12] analyzed and evaluated the slotted CSMA/CA to validate whether it is suitable for low cost and low-power consumption or not under saturated and unsaturated conditions. Lee et al [14] presented an additional carrier sensing (ACS) algorithm for IEEE 802.15.4 WSNs which gives the node one more chance that performs CCA if and only if the second CCA of the device is busy. Chong et al [15] analyzed the performance of throughput and energy consumption of ZigBee sensor networks under wireless local area network (WLAN) interference.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, the authors in [15] have designed one Additional Carrier Sensing (ACS) algorithm to reduce energy consumptions by avoiding further channel access through the information during the second CCA. However, the wastage of energy is possible when the second CCA is found busy due to data transmission.…”
Section: Related Workmentioning
confidence: 99%
“…A short clear channel assessment was then proposed to shorten the carrier sensing and increase the transmission attempts. Lee et al [83] identified the same inefficiency issue of double carrier sensing and proposed a 3-slot clear channel assessment method to differentiate between data packet and acknowledgment packet. The knowledge on the type of packets results in better transmission strategy and hence higher throughput and lower energy consumption.…”
Section: Distributed Optimization Using Local Informationmentioning
confidence: 99%